Revefenacin, a once-daily, lung-selective, long-acting muscarinic antagonist for nebulized therapy: Safety and tolerability results of a 52-week phase 3 trial in moderate to very severe chronic obstructive pulmonary disease. (July 2019) - Donohue, James F.; Kerwin, Edward; Sethi, Sanjay; Haumann, Brett; Pendyala, Srikanth; Dean, Lorna; Barnes, Chris N.; Moran, Edmund J.; Crater, Glenn
Abstract: Background: Prior replicate 12-week phase 3 trials demonstrated that once-daily doses of revefenacin inhalation solution at 88 μg and 175 μg produced significant bronchodilation over 24 h post dose in patients with moderate to very severe chronic obstructive pulmonary disease (COPD). The objective was to characterize the safety profile of revefenacin 88 μg and 175 μg over 52 weeks of treatment. Methods: In this randomized, parallel-group, 52-week trial (NCT02518139), 1055 participants with moderate to very severe COPD received revefenacin 88 μg or 175 μg in a double-blind manner, or open-label active control tiotropium. Results: Treatment-emergent adverse events (AEs) were comparable across all treatment groups (n [%] patients; revefenacin 88 μg, 272 [74.7%]; 175 μg, 242 [72.2%]; tiotropium, 275 [77.2%]). Numerically fewer COPD exacerbations (n [%] patients) were observed with revefenacin 175 μg (73 [21.8%]) than with 88 μg (107 [29.4%]) or tiotropium (100 [28.1%]). Serious AEs were comparable with revefenacin 88 μg (58 [15.9%] and tiotropium (58 [16.3%]), but were lower with revefenacin 175 μg (43 [12.8%]), and mortality was low. In patients using revefenacin 88 μg or tiotropium with a concurrent long-acting β-agonist (LABA) product, the incidence of AEs was slightly higher than without concurrent LABA. LABA did not affect the incidence of AEs for patients who received revefenacin 175 μg. Conclusions: Revefenacin was generally well tolerated over 52 weeks of treatment, and had a safety profile that supports its use as a long-term once-daily bronchodilator for the nebulized treatment of COPD. Graphical abstract: Treatment-emergent adverse effects reported for >5% of patients that received revefenacin 175 μg and tiotropium 18 μg.Image 1 Highlights: Revefenacin's safety profile with/without concurrent LABA for 1 year was assessed. AEs and SAEs incidences were lowest with revefenacin 175 μg vs tiotropium. There were fewer COPD exacerbations with revefenacin 175 μg vs tiotropium. Concurrent LABA did not affect the incidence of AEs in the revefenacin 175 μg arm. Revefenacin may be a therapeutic option for a broad population of COPD patients.